Bringing culture to the masses : control, compromise and participation in the GDR - Richthofen, Esther von (Monographs in German history, 2009)
Introduction -- Nonconformity, coercion and alienation: the 1950s -- Neither puppets nor opponents -- Organising culture: compromise and communication -- Patterns of participation -- Communication with cultural functionaries -- Responding to developments at the grass roots -- From art to culture -- Breakdown of communication: the late 1970s and 1980s -- Conclusion